2019
DOI: 10.1016/j.rasd.2019.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Personal experiences disclosed by parents of children with Autism Spectrum Disorder: A YouTube analysis

Abstract: The current study used YouTube as a data source in order to observe parents of children with ASD speaking about their experiences in a 'naturalistic' setting. Fifty videos made by parents of children with ASD were collected and qualitatively analysed using a content analytic procedure. This revealed a number of common themes expressed by the parents about their experiences across these video clips. The topics mentioned most were Issues of self; Issues with the child; Relationships; Autism and daily life; Solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 57 publications
0
37
0
Order By: Relevance
“…For this reason, professionals from educational and health fields should emphasize that autism is a condition and not a disease that can be cured. Previous research has found that when searching “curing autism” on YouTube, 2500 results were obtained, most of them with higher views than “living with ASD” videos [ 9 ]. As the authors of this study want to emphasize, videos that purport cures may initiate false hope in parents, preventing them from accepting and coping with the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For this reason, professionals from educational and health fields should emphasize that autism is a condition and not a disease that can be cured. Previous research has found that when searching “curing autism” on YouTube, 2500 results were obtained, most of them with higher views than “living with ASD” videos [ 9 ]. As the authors of this study want to emphasize, videos that purport cures may initiate false hope in parents, preventing them from accepting and coping with the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The videos on YouTube that deal with this disorder often use children, youths, and adults with autism as the protagonists [ 1 , 7 ], as well as the families of children with this diagnosis, all of whom narrate their experiences from their own perspectives [ 8 , 9 ]. Several organizations, specialized in autism, upload videos on this site, in which experts such as teachers, pediatricians, or psychologists, discuss fundraising events, interventions, and therapies, among other information [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…YouTube is also used by social scientists as a source of public evidence about a topic, even though the site itself is not relevant to the enquiry. For example, teams have investigated parents' video reactions to their children's autism diagnosis (Lloyd;Osborne;Reed, 2019), family reactions to being affected by the opioid crisis in the US (Johnson;Worth;Brookover, 2019), and squirrel videos to help understand their behaviour (Jagiello;Dyderski;Dylewski, 2019). Many articles are also hybrid, discussing the YouTube aspect of a wider issue, such as the representation of medical aspects of gender transformation (Miller, 2019).…”
Section: Youtubementioning
confidence: 99%